The efficacy of an oral formulation of Glycyrrhiza glabra, Viola odorata, and Operculina turpethum as an add-on therapy for mild-to-moderate childhood asthma: A randomized placebo-controlled clinical trial - Faezeh Rabbani; Mohsen Raeisi; Majid Keivanfar; Ali Saffaei; Ali Mohammad Sabzghabaee (Wolters Kluwer Medknow Publications, 2022)
Objective: We aimed to evaluate the efficacy of an oral combined tablet of Glycyrrhiza glabra, Viola odorata, and Operculina turpethum (Anti-Asthma®) as an add-on therapy for the relief of the severity of symptoms in mild-to-moderate childhood asthma. Methods: This randomized placebo-controlled clinical trial was performed on 60 children and adolescents with chronic mild-to-moderate childhood asthma. Patients were randomly divided into cases who received Anti-Asthma® oral combined tablets 2 tablets twice dailt for 1 month and controls, received placebo tablets identically the same to Anti-Asthma® (2 tablets, twice daily, for 1 month) as add-ons to their standard therapy according to the guideline. The severity and frequency of cough attacks and shortness of breath, respiratory test indices (based on spirometry), and the extent of disease control and treatment adherence were measured clinically by validated questionnaires at the beginning and after the study. Findings: Respiratory test indices improved and the severity of activity restriction decreased significantly in the cases compared to the controls However, the mean difference before and after the study was significantly different between the cases and controls only for the number and severity of coughs and the severity of activity restriction. In the scores of the Asthma Control Questionnaire, the cases group had a significant improvement compared to the controls. Conclusion: Anti-Asthma® oral formulation may be effective as an adjunct add-on treatment in the maintenance therapy of mild-to-moderate childhood asthma.